The use of Qigong and Tai Chi in the management of temporomandibular joint dysfunction: A systematic review - Afeez A. Salami; Kehinde K. Kanmodi; Dhanushka Leuke Bandara; Timothy O. Aladelusi; Jimoh Amzat; Dan Lin; Temitope O. Ojo; Ruwan D. Jayasinghe (Health Science Reports, 2023)
Abstract Background and Aims Qigong and Tai Chi (QTC) are mind‐body exercises involving a sequence of graceful movements, which promote self‐healing, meditation, and self‐cultivation. There is growing evidence that Qigong and/or Tai Chi therapy may improve the physical and psychological health among adults with multiple health conditions including joint movement. This systematic review aims to synthesize the available evidence on the type and effectiveness of QTC therapies used in the management of temporomandibular joint (TMJ) dysfunction. Methods This systematic review followed the AMSTAR‐2 guideline, and it was reported based on guidelines in the PRISMA checklist. The review involved a systematic search of nine electronic databases. After deduplication and screening of the literature retrieved from the search, only one article was included based on the review's inclusion criteria. Data was extracted from this article and synthesized. Results The only included article was on a non‐randomized control trial which investigated the role of Tai Chi Qigong (a form of Qigong) therapy in improving joint mobility and alleviating trismus among 52 survivors of nasopharyngeal carcinoma who had TMJ disorders. The study reported, at different time intervals (at pretest; at mid‐intervention; at posttest; and at follow‐up posttest), that no significant difference (p > 0.05) was observed concerning mouth opening capacity between the intervention group and the control group. However, over time, less severe deterioration in mouth‐opening was noted among the participants in the intervention group (p = 0.181) as compared to the control group (p < 0.001). Conclusion The role of QTC therapies in improving joint mobility and alleviating trismus is not yet fully understood, but it seems promising. The available evidence is inadequate to categorically conclude on the efficacy of these therapies. Further studies will be required to fully assess the effectiveness of QTC therapies in the management of TMJ dysfunction.